A time-parallel multigrid method for two-phase Stefan problems - Hoppe, Ronald H. W. 1951-; Wagner, Frank (1993)
Abstract: "We present time-parallel multigrid methods for the efficient numerical solution of moving boundary problems of two-phase Stefan type describing heat transfer processes with a change of phase. Using either a direct approach to the nonlinear enthalpy formulation of the problem or a linearization thereof based on semigroup theory, parallelism comes in by the simultaneous application of multigrid methods to a sequence of backward Euler steps in time. Numerical results obtained by the implementation of the algorithm on the Alliant FX/2800 are given in terms of various efficiency rates."
Keywords: Boundary value problems; Heat -- Conduction; Multigrid methods (Numerical analysis); Paralllel processing (Electronic computers)